The Antimicrobial Activity of Extracted Shiga Toxin from E. coli O157:H7 on Different Types of Bacteria and Fungi - Khutheir Abbas Ali; Harith Basim Ibrahim Al-Nasiri; Ola Hassan AlSaady (Academia Open, 2026)
General Background: Shiga toxin–producing Escherichia coli O157:H7 is a major foodborne pathogen associated with severe human disease and increasing antimicrobial resistance. Specific Background: Bacterial toxins have gained attention as alternative antimicrobial agents, yet their activity depends strongly on effective purification and characterization. Knowledge Gap: Limited evidence is available regarding the antimicrobial spectrum of purified Shiga toxin against diverse bacterial and fungal pathogens isolated from food sources. Aims: This study aimed to isolate E. coli O157:H7 from dairy and meat products in Baghdad and to evaluate the antimicrobial activity of purified Shiga toxin. Results: Thirty E. coli O157:H7 isolates were obtained from 300 samples. Shiga toxin was successfully purified using ammonium sulfate precipitation, dialysis, and ion-exchange chromatography, and showed inhibitory activity against several pathogenic bacteria and Candida albicans, with the lowest MIC observed for the fungus. Novelty: The study demonstrates selective antimicrobial efficacy of purified Shiga toxin against both bacterial and fungal pathogens. Implications: These findings highlight the potential of bacterial toxins as candidate agents for controlling foodborne and multidrug-resistant microorganisms. Keywords : Shiga Toxin, Escherichia coli O157:H7, Antimicrobial Activity, Ion-Exchange Chromatography, Foodborne PathogensHighlight : Purified toxin showed strongest growth inhibition against Candida albicans at the lowest tested concentration. Meat-derived samples exhibited higher contamination rates compared with dairy products. Selective susceptibility was observed, with Klebsiella pneumoniae demonstrating marked sensitivity.